The Impact of Sustainable Exhibition Standards on Attendee Satisfaction and Behavioral Intentions - Nakkham, Titinart; Silanoi, Tongrawee (KKBS Journal of Business Administration and Accountancy, 2023)
The objectives of this research were to investigate the impact of sustainable exhibition standards on attendee satisfaction and behavioral intention and the effect of attendees’ satisfaction affecting their behavioral intentions. The research is a quantitative study using survey questionnaires. The research used Descriptive Statistics, Factor Analysis, and Multiple Regression Analysis to analyze data sampling by 386 questionnaires. The result found that in Exploratory Factor Analysis (EFA), the variables of sustainable exhibition standards can be grouped as 1) Management, 2) Access, 3) Service, 4) Energy, 5) Waste, and 6) Food Waste. The Multiple Regression Analysis found that the variables of sustainable exhibition standards affected attendee satisfaction and behavioral intentions except for the food waste, with a statistical significance level at 0.05